Geometrical optics methods for moving anisotropic media: a tool for magnetized plasmas - Braud, Aymeric; Langlois, Julien; Gueroult, Renaud (Comptes Rendus. Physique)
The propagation of a wave in a medium is generally affected when the medium is moving with respect to the observer. Because plasma equilibria often involve plasma flows, for instance in astrophysics or in magnetic confinement nuclear fusion devices, understanding the effect of motion on plasma waves is important. Meanwhile, the presence of a background magnetic field in a plasma makes it anisotropic. To address this problem, we derive here ray tracing equations for the trajectory of rays propagating in a moving anisotropic medium. The proposed approach is to use an effective dispersion relation for the moving medium as seen from the laboratory, obtained by performing a Lorentz transformation of the dispersion relation known for the medium at rest. This formalism is illustrated by considering the low frequency Alfvén waves and the standard ordinary and extraordinary modes in a magnetized plasma at rest.